The Effect Of Digital System Implementation On Taxpayer Compliance With Digital Culture As A Moderating Variable - Rika Lidyah; Wati Rosmawati; Yeni Indraningtyas; Endang; Nuraini (Jurnal Teknologi dan Manajemen Industri Terapan, 2024)
In an effort to increase state revenue and administrative efficiency, many global tax authorities, including Indonesia, have invested significant resources in implementing Digital Tax Systems (e.g., e-filing, e-billing, e-invoice, and core tax systems). The implementation of these systems aims to simplify the reporting process, reduce compliance costs, and minimize human interactions that are prone to corruption, thereby ultimately improving Taxpayer Compliance. However, the effectiveness of these digital systems is not universal and is predicted to depend heavily on the user's context. This study aims to examine the role of taxpayer Digital Culture, defined as a combination of digital literacy, trust in technology, and acceptance of process automation, as a moderating variable in the relationship between Digital System Implementation and Taxpayer Compliance. Using a quantitative approach with a hierarchical regression model (Moderated Regression Analysis) or PLS-SEM, this study tests the hypothesis that the positive impact of digital system implementation on compliance will be significantly more substantial among taxpayers with a high Digital Culture and, conversely, weaker among those with a low Digital Culture. These findings are expected to provide strategic implications for the Directorate General of Taxes (DGT) in designing targeted education and outreach programs to ensure that technology implementation reaches its maximum potential in driving compliance.